2017
DOI: 10.1093/humrep/dew342
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive experiences of women who cryopreserved oocytes for non-medical reasons

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 32 publications
5
78
0
4
Order By: Relevance
“…Despite recommendations, the mean age of women who choose to bank their eggs is high, both internationally and in our report. In a Spanish setting, the mean age at vitrification was 37.7 years, and corresponding data for Australia were 37.1 years . These results are similar to those of the present study with a mean age at vitrification of 36.9 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite recommendations, the mean age of women who choose to bank their eggs is high, both internationally and in our report. In a Spanish setting, the mean age at vitrification was 37.7 years, and corresponding data for Australia were 37.1 years . These results are similar to those of the present study with a mean age at vitrification of 36.9 years.…”
Section: Discussionsupporting
confidence: 90%
“…In our material, 15% of the women returned for autologous IVF. In a recent Spanish study, the usage was around 9% during a similar time span, and in a follow up in Australia by Hammarberg et al, only 6 women (6%) had used their stored oocytes, of whom 3 had given birth . Given that the majority of oocytes will never be used, it can be questioned whether elective egg freezing is cost‐effective.…”
Section: Discussionmentioning
confidence: 97%
“…For women who face an immediate loss of fertility, the choice to undertake this procedure is understandable. However, there is now rising interest in using OC as a way to delay childbirth in healthy women [16].…”
Section: Preservation Of Fertilitymentioning
confidence: 99%
“…Despite this, many recently surveyed women are in support of using oocyte cryopreservation as a means for extending fertility, but this openness towards the procedure has yet to translate into data [19]. A recent survey of 96 healthy Australian women who had opted for OC indicated that only 6 returned for the oocytes; of those, only half succeeded in giving birth [16]. The mean age for this cohort, however, was 37 years for oocyte freezing, which is past the point of peak fertility, and the small sample size makes this study only minimally effective at demonstrating the potential of OC for young, healthy women hoping to extend their fertility.…”
Section: Preservation Of Fertilitymentioning
confidence: 99%
See 1 more Smart Citation